Estimates of direct and maternal genetic effects for weights from birth to 600 days of age in Nelore cattle - De Albuquerque, L. Galvão [UNESP]; Meyer, K. (Wiley, 2001)
Estimates of direct and maternal variance and heritability for weights at each week (up to 280 days of age) and month of age (up to 600 days of age) in Zebu cattle are presented. More than one million records on 200 000 animals, weighed every 90 days from birth to 2 years of age, were available. Data were split according to week (data sets 1) or month (data sets 2) of age at recording, creating 54 and 21 data sets, respectively. The model of analysis included contemporary groups as fixed effects, and age of dam (linear and quadratic) and age of calf (linear) effects as covariables. Random effects fitted were additive direct and maternal genetic effects, and maternal permanent environmental effect. Direct heritability estimates decreased from 0.28 at birth, to 0.12-0.13 at about 150 days of age, stayed more or less constant at 0.14-0.16 until 270 days of age and increased with age after that, up to 0.25-0.26. Maternal heritability estimates increased from birth (0.01) to a peak of 0.14 for data sets 1 and 0.07-0.08 for data sets 2 at about 180-210 days of age, before decreasing slowly to 0.07 and 0.05, respectively, at 300 days, and then rapidly diminished after 300 days of age. Permanent environmental effects were 1.5 to four times higher than genetic maternal effects and showed a similar trend.
Keywords: Animalia; Bos indicus; Bos taurus